2013
DOI: 10.1063/1.4801739
|View full text |Cite
|
Sign up to set email alerts
|

Implicit measurement of the latent heat in a magnetocaloric NiMnIn Heusler alloy

Abstract: The latent heat linked with the first-order transformation of a NiMnIn Heusler alloy has been studied through direct measurements of the adiabatic temperature change, ΔTad, during magnetization process. The experimental procedure used guarantees independent data points and negates any contribution of hysteretic losses to the magnetocaloric effect. Thus, the differences between the magnitudes of ΔTad measurements during the magnetization with the initial temperature change directions from low-to-high and high-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…In a closely related compound Ni 50 Mn 34.8 In 14.2 B, direct measurements of the magnetization and the differential scanning calorimetry have shown that Ni 50 Mn 34.8 In 14.2 B exhibits a magnetostructural first-order phase transition from a ferromagnetic martensitic phase to a paramagnetic austenitic phase [68]. In another example, measurements of the adiabatic temperature change and the latent heat in Ni 2 MnIn alloy revealed a transition from a FM to a FRM state that is also of the first-order [82]. The phenomenological Ginzburg-Landau theory for the description of the experimentally observed sequences of phase transitions in Ni 50 Mn 35 In 15 Heusler alloy is proposed by Zagrebin et al [83].…”
Section: Shape Memory Alloys: Properties Technologies Opportunitiesmentioning
confidence: 99%
“…In a closely related compound Ni 50 Mn 34.8 In 14.2 B, direct measurements of the magnetization and the differential scanning calorimetry have shown that Ni 50 Mn 34.8 In 14.2 B exhibits a magnetostructural first-order phase transition from a ferromagnetic martensitic phase to a paramagnetic austenitic phase [68]. In another example, measurements of the adiabatic temperature change and the latent heat in Ni 2 MnIn alloy revealed a transition from a FM to a FRM state that is also of the first-order [82]. The phenomenological Ginzburg-Landau theory for the description of the experimentally observed sequences of phase transitions in Ni 50 Mn 35 In 15 Heusler alloy is proposed by Zagrebin et al [83].…”
Section: Shape Memory Alloys: Properties Technologies Opportunitiesmentioning
confidence: 99%
“…Magnetostructural transitions, such as those occurring in magnetic Heusler alloys [4], imply the reversible (although generally hysteretic) structural change from a low entropy, low symmetry, and low temperature phase (i.e., martensite) to a high entropy, high symmetry, and high temperature phase (i.e., austenite). Unlike the former described transitions, magnetostructural ones present a latent heat of the transformation and can be thermally activated (i.e., the transition temperature can be shifted with the heating or cooling rate) [5]. The magnetic nature of the austenite and martensite phases is diverse.…”
Section: Introductionmentioning
confidence: 99%